2021
DOI: 10.3390/su14010208
|View full text |Cite
|
Sign up to set email alerts
|

Are ESG Shares a Safe Haven during COVID-19? Evidence from the Arab Region

Abstract: The world experienced significant changes in its social and economic lives in 2020–21. Major stock markets experienced an immediate decline. This paper attempts to examine the impact of COVID-19 on stock market performance as well as to identify the differences between the responses of ESG stocks and normal stocks to pandemic conditions in the Arab region. Daily time series for three years between March 2019 and March 2021 were collected for the S&P Pan Arab Composite index and S&P/Hawkamah ESG Pan Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Following prior research, we also used the sub-dimensions of ESG performance (i.e., El Khoury et al 2021 ; Engelhardt et al 2021 ), namely, environmental score, social score, and governance score. To measure the effect of the independent variable (COVID-19), we adopted the annual number of cases for each country as a primary measure (e.g., Mousa et al 2022 ; Hoang et al 2022 ), and then, we applied the natural logarithm to it. The scale of COVID-19 cases was used because the international health trend of increasing or decreasing the number of cases is accompanied by closures or openness, which affects business organizations’ performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following prior research, we also used the sub-dimensions of ESG performance (i.e., El Khoury et al 2021 ; Engelhardt et al 2021 ), namely, environmental score, social score, and governance score. To measure the effect of the independent variable (COVID-19), we adopted the annual number of cases for each country as a primary measure (e.g., Mousa et al 2022 ; Hoang et al 2022 ), and then, we applied the natural logarithm to it. The scale of COVID-19 cases was used because the international health trend of increasing or decreasing the number of cases is accompanied by closures or openness, which affects business organizations’ performance.…”
Section: Methodsmentioning
confidence: 99%
“…The continuing impact of the pandemic will lead to a negative effect on stock returns (Hoang et al 2022 ). At the same time, the impact of the pandemic is likely to be less harmful to companies with high ESG performance (Mousa et al 2022 ). Also, the strength of the company’s financial performance enhances ESG performance (Sharma et al 2020 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The relationship between the sustainable index of Australia and 14 other markets has been investigated using the dynamic conditional correlation (DCC) method (Tularam et al, 2010) and found a significant rise in correlation among the indices during the market crises. However, Mousa et al, 2022 found that the ESG index is less volatile and safer during the crisis period. Maraqa and Bein (2020) found the existence of spillover relationship among the sustainable stock index, stock index of European countries and crude oil prices using DCC multivariate generalized autoregressive conditional heteroskedasticity (MGARCH).…”
Section: Literature Reviewmentioning
confidence: 97%
“…The impacts of the COVID-19 pandemic on Arab capital markets were examined by analyzing both the normal index and the ESG (environment, society, and governance) index. It was found that COVID-19 caused a shock in both indexes (Mousa et al, 2022). For instance, some business enterprises applied digital tools and automation technologies in their operation to maintain usual business processes.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%